Evaluation of Cytotoxic and Tyrosinase Inhibitory Activities of 2-phenoxy(thiomethyl) pyridotriazolopyrimidines: In Vitro and Molecular Docking Studies - Abuelizz, Hatem A.; Anouar, El H.; Marzouk, Mohamed; Hasan, Mizaton H.; Saleh, Siti R.; Ahudhaif, Adi; Alburikan, Khalid A.; Al-Salahi, Rashad (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: The use of tyrosinase has confirmed to be the best means of recognizing safe, effective, and potent tyrosinase inhibitors for whitening skin. Twenty-four 2-phenoxy(thiomethyl)pyridotriazolopyrimidines were synthesized and characterized in our previous studies. Objective: The present work aimed to evaluate their cytotoxicity against HepG2 (hepatocellular carcinoma), A549 (pulmonary adenocarcinoma), MCF-7 (breast adenocarcinoma) and WRL 68 (embryonic liver) cell lines. Methods: MTT assay was employed to investigate the cytotoxicity, and a tyrosinase inhibitor screening kit was used to evaluate the Tyrosinase (TYR) inhibitory activity of the targets. Results: The tested compounds exhibited no considerable cytotoxicity, and nine of them were selected for a tyrosinase inhibitory test. Compounds 2b, 2m, and 5a showed good inhibitory percentages against TYR compared to that of kojic acid (reference substance). Molecular docking was performed to rationalize the Structure-Activity Relationship (SAR) of the target pyridotriazolopyrimidines and analyze the binding between the docked-selected compounds and the amino acid residues in the active site of tyrosinase. Conclusion: The target pyridotriazolopyrimidines were identified as a new class of tyrosinase inhibitors.
Keywords: MCF-7